SARM1 is essential for NMDA receptor-dependent endocytosis of AMPA receptors in hippocampal neurons - Misaki Morishita; Shinji Matsuda (Neuroscience Research)
Long-term depression (LTD) is a form of synaptic plasticity thought to be the cellular basis of experience-dependent learning and memory. LTD is caused by an activity-dependent decrease in cell surface α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-type glutamate receptors (AMPA receptors) at the postsynaptic sites. However, the mechanism through which AMPA receptors are removed from the cell surface via neuronal activity is not fully understood. In this study, we showed that small interfering RNA (siRNA)-mediated knockdown of sterile alpha and toll/interleukin receptor motif containing 1 (SARM1) in cultured hippocampal neurons prevented the N-methyl-d-aspartate (NMDA)-induced reduction in cell surface AMPA receptors. However, the control RNA did not affect NMDA-mediated AMPA receptor trafficking. Overexpression of the siRNA-resistant form of SARM1 in SARM1-knocked-down neurons restored AMPA receptor trafficking. However, overexpression of SARM1, which lacks the mitochondrial transport signal, in the SARM1-knocked-down neurons did not restore NMDA-dependent AMPA receptor endocytosis. Moreover, the inhibition of the NADase activity of SARM1 blocked the NMDA-induced reduction of cell surface AMPA receptors. These results suggest that both the mitochondrial localization and NADase activity of SARM1 are essential for NMDA receptor-dependent AMPA receptor internalization in the hippocampal neurons.